Teaching young children - Henniger, Michael L.; National Association for the Education of Young Children (Upper Saddle River, N.J. : Merrill/Pearson, 2009)
Never HIGHLIGHT a Book Again! Includes all testable terms, concepts, persons, places, and events. Cram101 Just the FACTS101 studyguides gives all of the outlines, highlights, and quizzes for your textbook with optional online comprehensive practice tests. Only Cram101 is Textbook Specific. Accompanies: 9780135137468. This item is printed on demand.
Includes bibliography reference and index.
Keywords: Early childhood education